Gender (in)equality in Chilean press: journalists and sources - Mensa, Marta (2021)
Who writes the news in the Chilean press according to gender? Who are the sources, male or female, in the Chilean press? Is there a relationship between the gender of journalists and the gender of the sources in the Chilean press? This article studies the gender of the Chilean newsroom and their sources in 12,113 news through a quantitative method with a computational social science approach. This method combines web scraping and natural language processing techniques to gather and preprocess data, facilitating the exploration of complex social phenomena. Results show important biases in journalists and source gender. From a sample of 158 journalists, 99 were men (63%) and 59 women (37%). Also, from 12,113 news, 7,565 (62%) were written by male and 4,548 (38%) by female journalists. Of the 12,334 sources mentioned in the news, 9,771 were men (79%) and 2,563 were women (21%). A significant finding is that equality in the newsroom is related to how female and male journalists choose their sources. In other words, when a media has a newsroom with gender equality, the sources of the journalists are more equitable too. These results have important insights to discuss within the journalism schools, to make students aware of the gender bias in the profession. Furthermore, if the presence of female – journalists or sources- increased in the media, it would allow them to grow their media power and status.